1956
DOI: 10.2134/agronj1956.00021962004800030011x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Resistance to Fusarium Wilt of Flax in Punjab 531

Abstract: Synopsis Punjab 53, which is a composite of wilt resistant selection; of flax stemming from a single plant of Punjab, is resistant to some clone; of wilt because of two complementary genes FUA and FUB—A and B for convenience. The original plant of Punjab apparently had the genotype AaBB or AABb. A third gene FuC was found in Dakota 48–94 that would account for much of its resistance to one clone of wilt highly pathogenic on Punjab 53.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Consequently, accessions with resistance in the present study may not be resistant in India. In another investigation, resistance to fusarium wilt found in the flax accession 'Punjab 53' from India by Knowles et al (1956) was not confirmed when exposing the accession to a Russian pathogen population (Rozhmina, 2004). This indicates geographic variation in pathogen populations and virulence.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, accessions with resistance in the present study may not be resistant in India. In another investigation, resistance to fusarium wilt found in the flax accession 'Punjab 53' from India by Knowles et al (1956) was not confirmed when exposing the accession to a Russian pathogen population (Rozhmina, 2004). This indicates geographic variation in pathogen populations and virulence.…”
Section: Discussionmentioning
confidence: 96%